Basal cell carcinoma induced by therapeutic radiation for tinea capitis—clinicopathological study. Issue 1 (2nd May 2018) - Oshinsky, Shlomit; Baum, Sharon; Huszar, Monica; Debby, Assaf; Barzilai, Aviv
Abstract : Aims: An increased prevalence of aggressive histological subtypes, such as micronodular and morpheaform, has been seen, irrespective of the clinical course, in basal cell carcinoma (BCC) following irradiation for tinea capitis. The aim of this study was to assess the histopathological features of BCCs among patients irradiated for tinea capitis and correlate them with the clinical course. Methods and results: The medical records and BCC biopsy specimens of individuals who were previously irradiated for tinea capitis were reviewed. Demographic data and clinical characteristics were retrieved. Biopsy specimens were evaluated for histological subtype classification and additional histopathological features. A telephone survey was conducted to assess the clinical behaviour of the tumours. Thirty‐one patients (17 male; 14 female) were included. The average age at time of first biopsy was 56 years. The total number of lesions was 185, with 80% of subjects showing multiple lesions. The nodular subtype was the most prevalent, followed by superficial, micronodular and mixed tumours. One‐third of the BCCs could be classified as aggressive histologically. Stromal fibroplasia and melanin deposits were common. There was no mortality related to BCC. None of the 17 patients who completed the survey had evidence of local invasiveness or metastases. Conclusions: BCCs following radiation therapy for tinea capitis show unique histological characteristics related to aggressive behaviour. These aggressive features did not reflect the clinical behaviour in the current cohort.